Patient engagement in research with older adults with cancer. Issue 6 (November 2017) - Puts, Martine T.E.; Sattar, Schroder; Ghodraty-Jabloo, Vida; Hsu, Tina; Fitch, Marg; Szumacher, Ewa; Ayala, Ana Patricia; Alibhai, Shabbir M.H.
Abstract: Objective: Cancer is a disease that mostly affects older adults. Older adults have been under-represented in clinical cancer research. Around the world there is a push for patient engagement on study teams as it is anticipated to improve study design, recruitment and dissemination of findings. In the current overview we examined the evidence with regard to: 1) the history of patient engagement in research and frameworks developed; 2) impact of patient engagement on patient and research outcomes; 3) use of patient engagement in geriatrics and oncology, 4) recommendations for successful engagement; and 5) gaps in the literature that should be studied further. Methods: A narrative review was conducted. Articles published in English were searched in Medline with the help of a librarian. Results: Patient engagement has been shown to improve the conduct of studies by making the study design more relevant and feasible, and improving recruitment rates and uptake of research findings by patients. However, the best way to engage patients is not clear yet. Several resources have been developed to support researchers engaging older adults with cancer in research. Conclusions: While patient engagement in research seems promising to improve study outcomes, little evidence is available thus far in geriatric oncology settings. Several gaps in the literature are identified that should be further studied to determine the value of, and best approaches to, patient engagement with older adults with cancer.